Pengaruh Arus Kas Pendanaan Laba Bersih Dan Leverage Terhadap Financial Distress Dengan Profitabilitas Sebagai Variabel Moderasi: Studi Empiris Bursa Efek Indonesia - Ryan Sukandi Sarumaha; Fitri Yeni; Yosi Puspita Sari; Riri Mayliza (JURNAL PUNDI, 2021)
Fast traslate Icon translate  This study aims to determine the effect of  financing Activities of cash flow, net income and leverage on financial distress. The object in this study is the Indonesia Stock Exchange with a population is manufacturing companies on the IDX in 2015-2019 with a purposive sampling technique, so that the sample in this study amounted to 43 companies. The results of the study found that leverage had a negative effect on financial distress, while financing Activities of cash flow and net income had no effect on financial distress. The results of the study for the moderating variable found that profitability was only able to moderate the relationship between leverage and financial distress, while profitability was unable to moderate the relationship between financing Activities of cash flow and net income with financial distress.